Impact of baseline renal function on all‐cause mortality in patients who underwent cardiac resynchronization therapy: A systematic review and meta‐analysis. Issue 5 (1st May 2017) - Bazoukis, G.; Letsas, K.P.; Korantzopoulos, P.; Thomopoulos, C.; Vlachos, K.; Georgopoulos, S.; Karamichalakis, N.; Saplaouras, A.; Efremidis, M.; Sideris, A.
Abstract: Background: Cardiac resynchronization therapy (CRT) improves both morbidity and mortality in selected patients with heart failure and increased QRS duration. However, chronic kidney disease (CKD) may have an adverse effect on patient outcome. The aim of this systematic review was to analyze the existing data regarding the impact of baseline renal function on all‐cause mortality in patients who underwent CRT. Methods: Medline database was searched systematically, and studies evaluating the effect of baseline renal function on all‐cause mortality in patients who underwent CRT were retrieved. We performed three separate analyses according to the comparison groups included in each study. Data were analyzed using Review Manager software (RevMan version 5.3; Oxford, UK). Results: We included 16 relevant studies in our analysis. Specifically, 13 studies showed a statistically significant higher risk of all‐cause mortality in patients with impaired baseline renal function who underwent CRT. The remaining three studies did not show a statistically significant result. The quantitative synthesis of five studies showed a 19% decrease in all‐cause mortality per 10‐unit increment in estimated glomerular filtration rate (eGFR) [HR: 0.81, 95% CI (0.73–0.90), p <0.01, 86% I 2 ]. Additionally, we demonstrated that patients with an eGFR<60 mL/min/1.73 m 2 had an all‐cause mortality rate of 66% [HR: 1.66, 95% CI (1.37–2.02), p <0.01, 0% I 2 ], which was higher than in those with an eGFR≥60 mL/min/1.73 m 2 . Conclusion: Baseline renal dysfunction has an adverse effect on‐all cause mortality in patients who underwent CRT.